Exposure to a High-Fat Diet during Early Development Programs Behavior and Impairs the Central Serotonergic System in Juvenile Non-Human Primates - Thompson, Jacqueline R.; Valleau, Jeanette C.; Barling, Ashley N.; Franco, Juliana G.; DeCapo, Madison; Bagley, Jennifer L.; Sullivan, Elinor L. (Frontiers in Endocrinology, 2017)
Perinatal exposure to maternal obesity and high-fat diet (HFD) consumption not only poses metabolic risks to offspring, but also impacts brain development and mental health. Using a nonhuman primate model, we observed a persistent increase in anxiety in juvenile offspring exposed to a maternal HFD. Post-weaning HFD consumption also increased anxiety and independently increased stereotypic pacing. These behavioral changes were associated with modified cortisol stress response and impairments in the development of the central serotonin synthesis, with altered tryptophan hydroxylase-2 mRNA expression in the dorsal and median raphe. Post-weaning HFD consumption decreased serotonergic immunoreactivity in area 10 of the prefrontal cortex. These results suggest that perinatal exposure to HFD consumption programs development of the brain and endocrine system, leading to behavioral impairments associated with mental health and neurodevelopmental disorders. Also, an early nutritional intervention (consumption of the control diet at weaning) was not sufficient to ameliorate many of the behavioral changes such as increased anxiety that were induced by maternal HFD consumption. Given the level of dietary fat consumption and maternal obesity in developed nations these findings have important implications for the mental health of future generations.